Updating Clinical Practice: Improving Perioperative Pain Management for Adeno-Tonsillectomy in Children - Juan Manuel Redondo-Enríquez; María Rivas-Medina; Manuel María Galán-Mateos (MDPI AG, 2024)
Background/Objective: Perioperative acute pain management in pediatric patients is essential to reduce complications. Adenoidectomy-Tonsillectomy are surgical procedures requiring pain control, and risk minimization for postoperative bleeding, nausea, and vomiting. Despite their known secondary effects, the use of opioid analgesics is still preponderant in pediatric perioperative management. We performed a comprehensive review on adeno-tonsillectomy perioperative pain management in children. We developed and implemented a multimodal analgesia protocol aimed to improve patients' pain management while consistently reducing opioids use. Methods/Results: relevant Information was summarized, then compared to our clinical needs. Learnings were used to create and implement a multimodal analgesia protocol that we use in patients 3-9 years-old undergoing adenoidectomy/tonsillectomy. The full protocol is presented. Analgesic strategies have emerged to reduce or avoid the use of opioids. Among these strategies, combining different non-opioid analgesics (Ibuprofen, Paracetamol, Metamizole) has been shown to be an effective and safe pharmacological strategy when implemented as part of perioperative multimodal analgesia protocols. Considerable evidence associating the use of NSAIDs with a bigger risk of postoperative bleeding does not exist. Conclusions: Perioperative management of adenotonsillectomy pain should include preventive and multimodal analgesia, which have shown to provide significantly more effective analgesia than some opioid regimens. Ibuprofen offers highly effective analgesia for postoperative pain, particularly when combined with acetaminophen.